Mukhalingam attached to Vasuki - Mumbai Archive Project Team (Jio Institute, 2024)
The mukhalingam is attached to the body of the coiled serpent (naga) Vasuki, which forms a protective hooded canopy. In the mythological story of the churning of the ocean (Samudra Manthan), Vasuki is used as the rope to churn the ocean of milk. The presence of Vasuki signifies Shiva's mastery over fear and death.